PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, JUMLAH KOMITE AUDIT DAN PROPORSI KEPEMILIKAN MASYARAKAT TERHADAP AUDIT DELAY DAYS - Pratiwi, Gabriela Niken; Aziza, Nurna; Halimatusyadiah, Halimatusyadiah (UNIB Press, 2020)
Audit Delay or in some studies referred to as audit reporting lag is the time difference between the end of the fiscal year (date of closing the book) with the date of issuance of the audit report (independent auditor's report). This study aims to provide empirical evidence regarding the influence of company size, company age, number of audit committees and the proportion of public ownership on the number of audit delay days. The research sample was chosen based on the purposive sampling method in all companies except banks and insurance listed on the Indonesia stock exchange. With the observation period from 2014 to 2018. The samples obtained were 112 companies with 560 observations. The results indicate that company size does not significantly influence the number of audit delay days. This study also found that the age of the company has a significant effect on the number of days of audit delay. Meanwhile, this study found that the number of audit committees does not significantly influence the number of audit delay days.